1987
DOI: 10.1002/hyp.3360010207
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the universal soil loss equation and field techniques for assessing soil erosion on a tropical alfisol in western Nigeria

Abstract: Four techniques for soil erosion assessment were compared over two consecutive seasons for bare‐fallow plots and a maize‐cowpea sequence in 1985 at IITA, Ibadan, Nigeria. The techniques used were: tracer (aluminium paint), nails (16 and 25), the rill method, and the Universal Soil Loss Equation (USLE). Soil loss estimated by these techniques was compared with that determined using the runoff plot technique. There was significantly more soil loss (P < 0·01) in bare‐fallow than in plots under maize (Zea mays) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Generally, the R L variable is critical since it gives a reflection on the spatial extent of rill erosion (e.g., total length of rills) hence its importance in assessment of the actual total soil loss in the target area. Other authors found that rill erosion played a more important role to overall soil loss amount than sheetwash contribution (Collins and Dunne, 1986;Mtakwa et al, 1987;Govers and Poesen, 1988;Herweg, 1996). Govers and Poesen (1988) stated that the importance of rill erosion to sediment yield was attributed to its progressive increase in supply of sediments to the runoff flow, unlike the sheet erosion that decreased because of the eminent sealing and compaction of the interill areas in time.…”
Section: Linking Current Erosion Indicators To Soil Lossmentioning
confidence: 96%
“…Generally, the R L variable is critical since it gives a reflection on the spatial extent of rill erosion (e.g., total length of rills) hence its importance in assessment of the actual total soil loss in the target area. Other authors found that rill erosion played a more important role to overall soil loss amount than sheetwash contribution (Collins and Dunne, 1986;Mtakwa et al, 1987;Govers and Poesen, 1988;Herweg, 1996). Govers and Poesen (1988) stated that the importance of rill erosion to sediment yield was attributed to its progressive increase in supply of sediments to the runoff flow, unlike the sheet erosion that decreased because of the eminent sealing and compaction of the interill areas in time.…”
Section: Linking Current Erosion Indicators To Soil Lossmentioning
confidence: 96%
“…Soil loss was measured using the graduated nail technique (Mtakwa, et al, 1987); vegetal cover for pineapple and cowpea was estimated using the ring method (Elwell, 1986), and by using a planimeter for the egusi-melon. These were summed for l.OmZ of the cropped area at different stages of crop growth.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is inhibited by the scarcity of available field data that permit the separation of rill and interrill erosion (Govers and Poesen, 1998;Kimaro et al, 2008). It was observed that the importance of rill erosion decreased with time, mainly due to an increase in permeability of the interrill with time though it is not a general phenomenon (Mtkawa et al, 1987). However, the opposite results that the relative importance of interrill erosion decreases with time were presented by other researchers (Govers and Poesen, 1998).…”
Section: Rill Initiationmentioning
confidence: 99%